Em busca da audiodescrição na Netflix: a garantia de usuário e a acessibilidade à pessoa com deficiência visual - Maia, Élida (2024)
The article will bring an analysis of the Netflix streaming platform to understand if audiovisual productions are being made available with accessibility to People with Visual Impairments and thus guaranteeing the visually impaired user to have social and cultural inclusion through the platform. It seeks to understand whether the user guarantee is guaranteed by Netflix by understanding the diversity of the public that pays for this service and how inclusion policies are dealing with diversity. The research is carried out through a bibliographical research and a case study on Netflix and accessibility for the visually impaired. Originating a result on the number of titles that are available with audio description and the comparison with the number of titles that the platform currently has. Making it clear that this data is rotating, as Netflix constantly changes its movies and series by adding or removing titles from its catalogue.